Thailand’s Eastern Economic Corridor and Foreign Direct Investment - Leelathawornsuk, Monchai; Peanprasert, Kanokporn (Journal of Applied Economics and Management Strategy, 2024)
Eastern Economic Corridor (EEC) development is a government policy aimed at boosting the economy of Thailand by promoting three provinces in the eastern region, namely Chonburi, Chachoengsao, and Rayong. This study explains the impact of the EEC on foreign direct investment (FDI) to Thailand through descriptive analytics and the gathering of data and statistics. The study found that the EEC helped attract more FDI into Thailand because it is an important investment promotion policy of Thailand. This can be observed in the rising number of projects and investment values requesting investment promotion in the EEC, which has a clear trend of increasing since 2018. After the establishment of the EEC, the average number of projects increased from 310 projects per year to 542.83 projects per year and the average investment value increased from 174,729.53 million baht per year to 379,338.28 million baht per year. Furthermore, the registered capital of foreigners applying for investment promotion in the EEC has increased compared to the period before the EEC was established. To attract increased FDI sustainably, the study recommends that the Board of Investment, which regulates and promotes investment in Thailand, review its policies and benefits to respond to the rapid changes in the world's situation. Public relations should also be accelerated so that foreign investors know the necessary information that shows Thailand's readiness to promote its economic development. This will help build a positive image of Thailand and encourage more FDI in the future.